Factors associated with a return to preinjury level of sport performance after anterior cruciate ligament reconstruction surgery - Webster, K. E.; McPherson, A. L.; Hewett, T. E.; Feller, J. A. (The American Journal of Sports Medicine, 2019)
Background: Many studies have investigated factors that predict a return to sport participation after anterior cruciate ligament (ACL) reconstruction, but it is unclear whether the same factors are associated with a return to preinjury level of sport performance. Purpose: To identify factors that contribute to an athlete`s return to preinjury level of performance after ACL reconstruction. Study Design: Cohort study; Level of evidence, 2. Methods: A cohort of 222 patients (132 male, 90 female) who had ACL reconstruction surgery and completed a 12-month postoperative assessment were followed out to a mean 3 years (range, 2-4 years) to determine whether they had returned to their self-reported preinjury levels of sport performance. Rates of return to preinjury performance were calculated. Measures that had been recorded at the 12-month postoperative review—demographic (age, sex), sport activity level (Marx Activity Rating Scale, return to competition sport), knee laxity, limb symmetry (single and triple crossover hop), subjective function/symptoms (International Knee Documentation Committee subjective), and psychological readiness (Anterior Cruciate Ligament Return to Sport After Injury scale)—were compared between patients who returned to their preinjury levels of performance and those who did not. Univariate and multivariate logistic regression models were also used to prospectively determine the association between these measures and return to preinjury level of sport performance. Results: A total of 135 (61%) patients reported that they had returned to their preinjury levels of performance, with return rates similar between males (59%) and females (63%) and between those who had returned to competition at 12 months (62%) and those who had not (60%). There was no significant age difference between patients who returned to their preinjury levels of sport performance and those who did not; however, higher psychological readiness (P < .0001), greater limb symmetry (P < .05), higher subjective knee scores (P = .01), and a higher activity level (P < .04) were all associated with a return to performance. In the multivariate model, psychological readiness was the only variable that remained a significant predictor (odds ratio = 1.03; 95% CI, 1.01-1.04; P < .0001). Conclusion: A majority of athletes who returned to sport after ACL reconstruction reported that their performance was comparable with preinjury. Having a greater psychological readiness to return during rehabilitation was the most significant predictor of a subsequent return to comparable performance.